Designer meat production, carcass quality, and hemato-biochemical parameters of broilers fed dietary synbiotic derived from trimmed asparagus by-products combined with probiotic supplementation (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This experiment investigated the effects of synbiotic supplementation produced from probiotics and prebiotics from trimmed asparagus by-products (TABP) on broiler chicken diets in order to yield designer meat production. Materials and Methods: A total of 320 one-day-old Ross 308® chicks were randomly allocated to dietary treatments with four replications each (n = 20). The dietary treatments were composed of a control group without supplementation and treatment groups fed with 10, 30, and 50 gm/kg of TABP supplementation in diets combined with 2 gm/kg probiotics. Results: The results showed that broilers fed dietary supplementation of TABP with 2 gm/kg had a lower level of total cholesterol and low-density lipoprotein cholesterol in the serum, which reduced the atherogenic indices of the serum, such as cardiac risk ratio and atherogenic coefficient (p < 0.05). In addition, the cholesterol content and the fatty acid profile of breast meat, including palmitic acid, oleic acid, saturated fatty acid, and omega 9 levels, also declined with the increasing levels of TABP inclusion (p < 0.05). Moreover, the supplementation of TABP in diets caused a decline in the atherogenic and thrombogenicity indices and a rise in Δ-9 desaturase (16) index and hypocholesterolemic to the hypercholesterolemic ratio of meat (p < 0.05). Conclusion: Synbiotic supplementation of up to 30 gm/kg TABP combined with 2 gm/kg probiotics in the chicken diet can potentially be utilized for the production of designer meat. J. Adv. Vet. Anim. Res., 8(3): 516–526, September 2022http://doi.org/10.5455/javar.2022.i621